Business Model for Sheep Market Information Service in Bonga, Ethiopia - Bereket, Yemariam; Solomon, Rahel; Asnake, Woinshet; Kassie, Girma (International Center for Agricultural Research in the Dry Areas, 2023)
This document presents a business model that can serve as a framework for entrepreneurs to establish profitable ventures that address the challenges faced by sheep keepers and other market actors. The key benefits for customers of this business will include understanding market trends, identifying potential buyers, and negotiating fair prices for their products.